99 Complexity and outcomes of paediatric patients cared for by a general community palliative care team. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Doherty, M; Cranfield, F; McLean, S
Abstract : Background: Despite development of specialist palliative care (SPC) services for paediatric patients (PPts) in Ireland, general community palliative care teams (CPCTs) provide a significant amount of palliative care to PPts at home. Outcomes describe the change in health status arising from healthcare interventions. Measuring outcomes helps evaluate clinical care, informs resource allocation, and drives quality improvement. In one CPCT, point of care collection of clinical and workload data has been routine since 2013. Data collected is used for clinical handover, measuring workload and complexity, and outcomes measurement. Aims and objectives: To describe the complexity, workload and outcomes of PPts under CPCT; to demonstrate the feasibility of standardised outcomes measurement in SPC. Methods: Validated assessments are performed at each review: Phase of illness; Problem Severity Score (PSS); Palliative Performance Scale (PPS); Visit duration; Healthcare professional (HCP) stress. Data collected between 2013 and May 2017 were analysed using descriptive and analytical statistics. Findings/results: For 201 episodes (17 PPts), the median duration of care was 7 days (range 1–350). 89.1% episodes were nursing visits; 95.2% at home. The care of PPts was more complex than of adult patients (APts). 43.4% of episodes were in stable phase. There was no difference in mean PSS between PPts and APts (4.59 vs 4.68/12). Caregivers of PPts had higher psychosocial symptom severity compared to caregivers of APts (1.66/3 vs 0.97/3). HCPs reported stress more frequently at visits to PPts than APts (26.4% vs 4.64% of visits). Higher HCP stress was moderately correlated with higher PSS (Pearson's r=0.347, p=0.001), caregiver psychosocial issues (r=0.282, p=0.001), and strongly correlated with patient psychosocial issues (r=0.392, p<0.001). Conclusions: PPts under the care of CPCTs are complex, and their care may present a challenge to general CPCts. The care of PPtx is associated with significant HCP stress. Routine outcomes measurement in CPC is feasible and useful.